Trends in Health Disparities, Health Inequity, and Social Determinants of Health Research: A 17-Year Analysis of NINR, NCI, NHLBI, and NIMHD Funding. Issue 3 (May 2018) - Kneipp, Shawn M.; Schwartz, Todd A.; Drevdahl, Denise J.; Canales, Mary K.; Santacroce, Sheila; Santos, Hudson P.; Anderson, Ruth
Abstract : Background: The theoretical landscape of health disparities research now emphasizes health inequities and the role that social determinants of health (SDOH) play in creating and perpetuating them. Whether National Institutes of Health (NIH) funding patterns reflect this theoretical shift is unknown. Objectives: The aim of this study was to examine the National Institute of Nursing Research's (NINR) funding for research focused on health disparities, health inequities, and SDOH, relative to other key NIH institutes. Methods: Data on 32, 968 projects funded by NINR, the National Cancer Institute, the National Heart, Lung, and Blood Institute, and the National Institute of Minority Health and Health Disparities (NIMHD) during the years 2000 through 2016 were downloaded from NIH RePORTER; those with health disparities, health inequity, or SDOH terms used in the abstract were identified. Descriptive statistics and a general linear model approach were used to assess differences in cumulative project counts and funding proportions, and funding trends over time. Results: Overall, funding for health disparities projects was 14–19 times greater than for health inequity and SDOH projects and was more concentrated in centers and institutional training than in individual research projects. NINR's proportion of funding for disparities projects was consistently greater than that of the National Cancer Institute and the National Heart, Lung, and Blood Institute, but not for inequities and SDOH projects. NIMHD's proportion of funding for disparities, and inequities and SDOH projects (combined) was 2–30 times greater than that of other institutes. Over the 16-year period, funding for disparities, inequity, and SDOH projects each increased (all p s < .05); however, growth in inequities and SDOH funding was not evident in more recent years. Discussion: Funding for projects focused on health equities and the SDOH lag behind theoretical shifts in the broader health disparities research arena. With the exception of NIMHD, there is a disconnect between funding for projects with a disparities orientation in institutional training and center projects relative to individual research projects. These trends have implications for nurse scientists seeking NIH funding to support health equity-oriented research.